Cubic aluminum nitride transformed under reduced pressure using aerosol deposition method - Iwata, A.; Akedo, J.; Lebedev, Maxim (BLACKWELL PUBLISHING, 2005)
Higher thermal conductivity is expected for cubic aluminum nitride that is very difficult to make. Thick aluminum nitride films that have mixed crystal structures of rock salt (cubic) and wurtzite are made at room temperature by aerosol deposition method. The maximum micro-Vickers hardness number is 1200. The primary powder has wurtzite structure, which indicates part of the original crystals is transformed. Only very small crystallites are transformed. The transformation is supposed to occur by shock of the particle impact on the film. The pressure at the impact is estimated to be only 7 GPa.